Perceived Stress and Coping Strategies among B.Sc. Nursing Students in Mizoram during COVID-19 Pandemic - C. Lalramdini; H. T. Lalremsanga; Lukima Saikia; H. T. Malsawmtluanga (Indian Journal of Psychiatric Nursing)
Background: During the COVID-19 pandemic, the education system was among the worst hit. The online education system was introduced, and students have to stay home surrounded by uncertainty of their future, leading to various levels of stress and the need to somehow cope with it. Materials and Methods: An online cross-sectional descriptive study involving 417 B.Sc. Nursing students were conducted between March 2, 2022 and March 8, 2022 to assess the perceived stress and coping mechanisms among Mizoram’s B.Sc. nursing students during the COVID-19 pandemic and to ascertain the association between stress and coping with specific demographic variables. To assess the level of stress and coping strategies, respectively, Pandemic-Related Perceived Stress Scale of Covid-19 (PSS-10-C) and Modified Brief-Coping orientation to problems experienced Scale were used. Results: The majority of the participants 89% were female, whereas 10.1% were male. Most of the participants 89.2% resided in a hostel. A high level of stress is seen among 2.15% of the participants. The majority 83.7% have moderate stress levels and a low level of stress is seen among 14.15% of the participants. Perceived stress is higher among the females significantly at 0.02 and also among those who reside in the hostel at 0.02 level. Among the participants with high perceived stress levels, avoidance coping is most adopted by a mean value of 25.00 (5.61). Conclusions: The findings suggest that there is a need for appropriate intervention for assisting the B.Sc. nursing students in stress management to adopt healthy coping strategies.